2017
DOI: 10.1073/pnas.1616340114
|View full text |Cite
|
Sign up to set email alerts
|

Defining recovery neurobiology of injured spinal cord by synthetic matrix-assisted hMSC implantation

Abstract: Mesenchymal stromal stem cells (MSCs) isolated from adult tissues offer tangible potential for regenerative medicine, given their feasibility for autologous transplantation. MSC research shows encouraging results in experimental stroke, amyotrophic lateral sclerosis, and neurotrauma models. However, further translational progress has been hampered by poor MSC graft survival, jeopardizing cellular and molecular bases for neural repair in vivo. We have devised an adult human bone marrow MSC (hMSC) delivery formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(114 citation statements)
references
References 61 publications
(111 reference statements)
2
111
0
1
Order By: Relevance
“…Any established hMSC line can be characterized following the procedures and parameters described in protocol. For our original studies, hMSC lines were established from cells obtained from either a 26-year-old male donor (7023-R) or a 29-year-old female donor (7038-L) at the Tulane University Center for Gene Therapy, an NIH-funded cell distribution center Ropper et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Any established hMSC line can be characterized following the procedures and parameters described in protocol. For our original studies, hMSC lines were established from cells obtained from either a 26-year-old male donor (7023-R) or a 29-year-old female donor (7038-L) at the Tulane University Center for Gene Therapy, an NIH-funded cell distribution center Ropper et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Current Protocols in Stem Cell Biology tailored with unique porous, soft, and smooth features to maintain the stemness biology of hMSCs (Ropper et al, 2017).…”
Section: Of 23mentioning
confidence: 99%
See 2 more Smart Citations
“…These non-toxic materials can be used to form robust bridges and scaffolds which facilitate nerve regeneration. Recent studies have also found that multiple poly (lactic-co-glycolic) channels can serve as bridges that physically direct the growth of axons across the injury while also optimizing the post-traumatic spinal cord microenvironment [78][79][80]. Numerous methods have been developed to synthesize bridges using natural or synthetic polymers [81], and certain biomaterials have been shown to provide neuroprotective benefits for SCI patients.…”
Section: Guided Axonal Regenerationmentioning
confidence: 99%